Quality of Social Services in Slovakia - Hromkova, Michaela (Civilia, 2013)
The area of social services is characterized by the high degree of diversity. There is the Act on social services in Slovakia which defines social services as professional, utility and other activities with main purpose to help people in need. The obligations of social services providers are also the part of this Act. According to the quality of social services, the main obligation of providers is to elaborate and observe procedural, personnel and operating conditions of providing social services, so - called standards of quality. Nowadays there are no standards for quality of social services in Slovakia. The theoretical basis of the evaluation of social services provides for example the evaluation theory. Very important is the evaluation of social services by clients' points of view.
Keywords: Social services; Quality of social services; Standards of quality; Evaluation of social services; Evaluation theory; Needs assessment